(untitled) (International Journal of Economics Management and Social Science, 2026)
Small and Medium Enterprises (SMEs) in bamboo handicrafts in Bangli Regency, Bali, play an important role in the local economy. However, they face various challenges, including limited access to markets, capital, and technology. The resilience of SMEs is key to overcoming these challenges, and social networks are a factor influencing business sustainability. This study uses the Social Network Analysis (SNA) approach to examine the positions of actors in social networks and their relationships to the resilience of bamboo handicraft SMEs in Bangli. The results of the study show that actors in central positions in the social network, such as craftsmen with high Betweenness Centrality (BC) values, have better adaptive capabilities and can access more resources.In contrast, actors with low BC values are isolated and less able to adapt to changes. A wide network of connections to various external actors strengthens SME resilience in the face of crises, including economic crises and market shifts. This research provides important insights into the significance of position within a social network for enhancing the resilience of SMEs, particularly in the handicraft sector, in a specific local context. Keywords : SMEs, resilience, social network, Social Network Analysis (SNA), bamboo handicrafts